PENGARUH PEMBERIAN TOPIKAL ASI TERHADAP WAKTU PERAWATAN TALI PUSAT PADA BAYI BARU LAHIR DI PUSKESMAS ANGKONA KECAMATAN ANGKONA KABUPATEN LUWU TIMUR - Andi St. Umrah (Voice of Midwifery, 2017)
Background: The umbilical cord aims to prevent infection and speed up cord removal from the abdomen. Objective: To determine the effect of topical breastfeeding on umbilical cord time in newborn at Angkona health center of Angkona Subdistrict of East Luwu Regency in 2017.Method: This research is a pre-experiment "with static group comparison group" research, population in research this is all newborns on the peroide of June - July at Angkona Health Center Subdistrict Angkona Regency Luwu Timur 2017 as many as 38 people. Sampling using total sampling, the sample was divided into two groups, namely the intervention group as much as 19 people and the control group of 19 people. Data collection using checklist sheet. The data collected were then processed and analyzed using univariate and bivariate analyzes ie chi-square test and multivariate analysis using logistic regression using statistic program (SPSS) version 20, table presented in table 2x2 form.Result: bivariate analysis found there is influence of topical giving of breast milk to umbilical cord care time, with value p = 0,000 <value of α = 0,05. Result of multivariate analysis obtained value OR = 14,15.Conclusion: There is an effect of topical breastfeeding on time of umbilical cord care at Angkona Health Centert of Angkona Subdistrict of East Luwu Regency in 2017, with p value = 0,001 <value of α = 0,05 and OR value = 14,15. Keywords:  Topical Breastfeeding, umbilical cord, Cord Care Time